Green synthesis of silver nanoparticles by Chrysanthemum morifolium Ramat. extract and their application in clinical ultrasound gel - He Y (Dove Medical Press, 2013)
Yan He,1 Zhiyun Du,1,2 Huibin Lv,1 Qianfa Jia,1 Zhikai Tang,1 Xi Zheng,1,3 Kun Zhang,1 Fenghua Zhao11Institute of Natural Medicine and Green Chemistry, School of Chemical Engineering and Light Industry, Guangdong University of Technology, Guangzhou, People’s Republic of China; 2State Key Laboratory of Natural and Biomimetic Drugs, Peking University, Beijing, People’s Republic of China; 3Susan Lehman Cullman Laboratory for Cancer Research, Department of Chemical Biology, Ernest Mario School of Pharmacy, Rutgers, The State University of New Jersey, Piscataway, NJ, USAAbstract: Eco-friendly green synthesis with plant extracts plays a very important role in nanotechnology, without any harmful chemicals. In this report, the synthesis of water-soluble silver nanoparticles was developed by treating silver ions with Chrysanthemum morifolium Ramat. extract at room temperature. The effect of the extract on the formation of silver nanoparticles was characterized by ultraviolet and visible absorption spectroscopy, X-ray diffraction, transmission electron microscopy, and Fourier transform infrared spectroscopy. The ultraviolet and visible absorption spectroscopy results show a strong resonance centered on the surface of silver nanoparticles (AgNP) at 430 nm. The Fourier transform infrared spectroscopy spectral study demonstrates Chrysanthemum morifolium Ramat. extract acted as the reducing and stabilizing agent during the synthesis. The X-ray diffraction analysis confirmed that the synthesized AgNP are single crystallines, corresponding with the result of transmission electron microscopy. Water-soluble AgNP, with an approximate size of 20 nm–50 nm were also observed in the transmission electron microscopy image. The bactericidal properties of the synthesized AgNP were investigated using the agar-dilution method and the growth-inhibition test. The results show the AgNP had potent bactericidal activity on Staphylococcus aureus and Escherichia coli, as well as a strong antibacterial activity against gram-negative bacteria, as compared to gram-positive bacteria with a dose-dependent effect, thus providing a clinical ultrasound gel with bactericidal property for prevention of cross infections.Keywords: silver nanoparticles, green synthesis, Chrysanthemum morifolium Ramat., bactericidal activity, ultrasound gel